Modificação da resposta inflamatória sistêmica em ratos inoculados com carcinossarcoma 256 de Walker : papel da degranulação mastocitária - Barbosa, André Luiz dos Reis (2007)
Our objective was to evaluate the effect of the 256 Walker carcinossarcoma inoculation, as well as the time course of tumoral development, upon the acute inflammatory response in rats. Wistar rats, 180-220g, received intramuscular 106 tumor cells injections. At the end of 4, 7 or 10 days, wistar rats were separated into 4 groups, with 6 animals per group. The control group, were not inoculated with tumoral cells. Several parameters were evaluated: paw edema induced by carrageenan (Cg; 300μg/hind) or dextran (Dxt, 500μg/hind paw), myeloperoxidase activity (MPO), neutrophil migration to peritoneal cavity induced by carrageenan, cutaneous vascular permeability induced by bradykinin (2μg/site), serotonin (1μg/site), histamine (30μg/site), substance P (250ng/site), capsaicin (50μg/site) or 48/80 compound (1 μg/site) and mast cell degranulation induced by 48/80 compound. Paw edema was evaluated in the contra lateral hind paw of the tumor and measured at 0, 1, 2, 3 and 4h for Cg, and 0, 30’, 1, 2, 3 and 4h.for Dxt by plethysmometry. Neutrophil migration was induced by Cg injection in the contralateral hind paw or in the peritoneal cavity. After 4h, rats were sacrificed and the skin of the hind paw was harvested to measure neutrophil infiltration by MPO assay. Neutrophil migration induced by Cg was also evaluated in the peritoneal cavity, with the total e differential leucocytes counted. In order to measure cutaneous vascular permeability, immediately after intradermic stimulus injections (bradykinin, histamine, serotonin, substance P, capsaicin or 48/80 compound) Evans Blue dye was administrated (0,1mL/100g of per animal) by endovenous route. After 30 min rats were sacrificed and the skin was harvested to evaluate Evans Blue extravasations by spectrofotometry. Mast cells degranulation was evaluated in the in mesentery incubated with 48/80 compound and colored with toluidine blue. Our results shows that, in animals inoculated with the carcinossarcoma, there was a significant inhibition in the Cg and Dxt- induced paw edema, with maximal effect at the 7th and 10th days. There were no differences in MPO activity and neither in the peritoneal neutrophil infiltration induced by Cg in rats inoculated with the carcinossarcoma when compares to normal animals. After 4 and 7 days of the tumor inoculation, we observed a significant inhibition of the vascular permeability induced only by bradikinin, serotonin and 48/80 compound.. In the 10th day after the carcinossarcoma inoculation, there was a significant inhibition of the vascular permeability induced by all inflammatory stimulus tested, when we compared animals not inoculated. Mast cell degranulation was decreased in the 4th, 7th and 10th days after carcinossarcoma inoculation. These results suggested that the tumor microenvironment decreased the acute inflammatory response probably due to a inhibition of the mast cell degranulation.